Supporting development efforts of clinical care teams. (1st January 2012) - Grippa, Francesca; Palazzolo, Margaret; Bucuvalas, John C.; Gloor, Peter A.
This paper describes the results of a longitudinal study of team communication structure for two distinct interdisciplinary healthcare teams at a large academic children medical centre in the USA. Our goal was to inform teams of opportunities and strategies that strengthen their communication structure. To this purpose we proposed an operational framework based on four steps: observation, measurement, mirroring and design. We analysed the e-mail archives of two teams to monitor structural changes in e-mail communication over one year. Since the first analyses, both teams were designated as strategic priorities by the institution, underwent off site meetings to define and put into execution a strategic plan, initiated processes to improve care delivery and reviewed the results of the initial social network analysis. We found that for both teams the communication network improved over time showing a higher cohesiveness, an increase in density, network resilience and external connectivity.